Oral Health Literacy—Measurement Instruments and their Psychometric Properties: A Systematic Review - Ramos-Pilco, Edwin; Sánchez-Tito, Marco Antonio; Yileng-Tay, Lidia (Puerto Rico Health Sciences Journal, 2023)
Objective: This article aims to provide an evaluation of the psychometric properties of the instruments of oral health literacy in adults. Methods: An electronic search for instrument studies was performed in the PubMed, PubMed Central, ScienceDirect, Scopus, EMBASE, and PsycINFO databases to find articles published up to June 2021. The risk of bias of the included studies was assessed using the COSMIN (COnsensus-based Standards for the selection of health Measurement INstruments) Risk of Bias checklist for systematic review. Results: From an initial sample of 2617 articles, 14 instrument studies were included in the present review. Their sample sizes ranged from 177 to 1405 adults, and the number of items per measurement instrument ranged from 14 to 99. For structural validity, statistical techniques were performed using the classical test theory (exploratory and confirmatory factor analysis) and the item response theory (dichotomous and polytomous models). The Rapid Estimate of Adult Literacy in Dentistry 30, elaborated in the USA, was the measurement instrument that had the greatest number of cultural adaptations, having been validated in such countries as Saudi Arabia, Brazil, Turkey, and Romania. The evaluation of the risk of bias, undertaken using the COSMIN Risk of Bias checklist, showed that 6 of the 10 parameters had been evaluated. Conclusion: The psychometric properties that were evaluated in the present systematic review were structural validity, internal consistency, reliability (test–retest), and hypothesis testing for construct validity. To date, there is no gold standard measuring instrument to evaluate the criterion validity parameter.